Investigation on applied automatic monitoring of deep foundation-pit projects. Issue 1 (October 2020) - Hu, Xiaolong; Huang, Zhixing; Geng, Pei
Abstract: A deep foundation-pit project in Shenzhen is studied for the application of automatic monitoring in the construction of deep foundation pit. Based on the analysis results of a three-dimensional finite element model implements with the MADIS GTS software, nine monitoring items and 59 automatic monitoring points are arranged in the key areas of the foundation pit, to monitor in real time the pit-top horizontal displacement, pit-top settlement, column pile settlement, groundwater level, horizontal displacement of deep layer, axial force in the supporting structure, anchor-cable stress, and settlement and cracks of the surrounding buildings. Based on the results of automatic monitoring, the patterns of variation are discussed of the data of the monitored items, and the accuracy and data stability are analyzed of the monitoring sensors such as measuring robot, hydrostatic level and crack gauge. The results show that: the key areas of automatic monitoring determined by the three-dimensional finite element model are in good agreement with the actual situation on site; Under the given conditions, the sensors such as measuring robot, hydrostatic level and crack gauge can meet the required monitoring accuracy, and the measured data has high stability; in addition, the sensor value is closely related to the ambient temperature. These results can provide reference for similar projects.